Cardiovascular disease threat and perceived efficacy of selected preventive behaviors among Polish men: an analysis based on the extended parallel process model - Katarzyna Domosławska-Żylińska; Dorota Włodarczyk; Magdalena Krysińska-Pisarek (Frontiers Media S.A., 2023)
Considering the low rate of preventive behaviors (5%), it is important to increase the effectiveness of actions that motivate the public to engage in health-promoting behaviors. The purpose of this study was to assess the way in which Polish men perceive the threat of cardiovascular diseases (CVDs) and the effectiveness of five preventive behaviors in the context of CVDs. We aimed to identify groups of recipients, based on the extended parallel process model (EPPM), for five preventive behaviors and to compare the identified groups in terms of selected characteristics. We conducted the survey in November 2022, using the computer-assisted web interviewing technique, on a representative sample of 1,000 men aged 18-65 years. Polish men showed relatively low levels of perceived susceptibility to CVDs (15.1%), but at the same time tended to perceive the consequences of CVDs as severe (54.2%). Segmentation of audiences according to the EPPM showed that regardless of the type of preventive behavior, the most numerous groups are responsive (31-37%) and indifferent (29-31%). This study revealed the need to increase awareness of the importance of a healthy diet to prevent CVDs among male population. Less than half of the men indicated that they would be able to implement effective stress management (49.8%) and smoking avoidance (39.4%), indicating the need to implement measures to increase self-efficacy in the areas.